Corporate reputation in B2B service customers: the effect on word of mouth, loyalty intentions and trust - Lourenço, Ana Filipa Mendes (2017)
The present investigation addresses the concept of corporate reputation as a vital asset for companies, which importance has increased particularly in regard to the perception of B2B customers in the service context. The lack of attention attributed to this pivotal stakeholder in this specific context was identified by Walsh et al. (2015) who developed the professional service firm reputation (PSF-Rep) scale, a measure that focusses in the B2B customers’ perception of reputation of professional services. Therefore, the main purpose of the current investigation is to replicate the PSF-Rep scale in a different environment, accessing its cross-cultural consistency and behaviour in a different industry. From a sample of B2B customers of the main postal operator in Portugal, the empirical analysis was performed through a series of statistical techniques, revealing the consistency of three of the original dimensions of PSF-Rep scale, and unveiling a new dimension – market superiority. The results also corroborate the dimensions’ influence in important customer behaviours, such as word of mouth, loyalty intentions and trust, although with the exception of one dimension, relational equity which revealed absence of relation with the three customer variables. Hence, this research contributes to the corporate reputation measurement, emphasising the urgency for companies to apply such tools in order to achieve and manage a good reputation, especially in the point of view of professional services, being crucial for maintaining and acquiring new customers.